Singing emotionally: a study of pre-production, production, and post-production facial expressions - Quinto, Lena R.; Thompson, William F.; Kroos, Christian; Palmer, Caroline (Frontiers in Psychology, 2014)
Singing involves vocal production accompanied by a dynamic and meaningful use of facial expressions, which may serve as ancillary gestures that complement, disambiguate, or reinforce the acoustic signal. In this investigation, we examined the use of facial movements to communicate emotion, focusing on movements arising in three epochs: before vocalisation (pre-production), during vocalisation (production), and immediately after vocalisation (post-production). The stimuli were recordings of seven vocalists’ facial movements as they sang short (14 syllable) melodic phrases with the intention of communicating happiness, sadness, irritation, or no emotion. Facial movements were presented as point-light displays to 16 observers who judged the emotion conveyed. Experiment 1 revealed that the accuracy of emotional judgement varied with singer, emotion and epoch. Accuracy was highest in the production epoch, however, happiness was well communicated in the pre-production epoch. In Experiment 2, observers judged point-light displays of exaggerated movements. The ratings suggested that the extent of facial and head movements is largely perceived as a gauge of emotional arousal. In Experiment 3, observers rated point-light displays of scrambled movements. Configural information was removed in these stimuli but velocity and acceleration were retained. Exaggerated scrambled movements were likely to be associated with happiness or irritation whereas unexaggerated scrambled movements were more likely to be identified as “neutral”. An analysis of the motions of singers revealed systematic changes in facial movement as a function of the emotional intentions of singers. The findings confirm the central role of facial expressions in vocal emotional communication, and highlight individual differences between singers in the amount and intelligibility of facial movements made before, during, and after vocalization.